Jump Technique versus Seton Method for Anal Fistula Repair: A Randomized Controlled Trial. Issue 6 (1st June 2022) - Khoshnevis, Jalaluddin; Cuomo, Roberto; Karami, Farzaneh; Dashti, Terifeh; Kalantar Motamedi, Alireza; Kalantar Motamedi, Mohammadreza; Azargashb, Eznollah; Aryan, Negaar; Sadeghi, Payam
Abstract: Background: The treatment of anal fistula has been a conundrum for surgeons over the years. Various methods such as fistulotomy, fistulectomy, seton, ligation of the intersphincteric fistula tract (LIFT), advancement flaps, fibrin glue, and plugs are well-known techniques. Yet, they may be followed by several considerable complications, including incontinency and recurrence. Methods: In this study, the outcomes of the "Jump" and "Seton" techniques are compared. A randomized controlled trial consisting of 130 cases with cryptoglandular anal fistula randomly sorted into two groups was conducted. Group A underwent the "Jump technique" while group B underwent the "Seton technique." Outcomes, incontinency and recurrences in particular, were evaluated after a year of treatment. Data were analyzed by Fisher Exact, Chi-Square and Mann Whitney Tests. Results: Group A with 65 cases underwent the "Jump technique" while group B with 65 cases underwent the "Seton Method." Recurrence was reported in 12 (20%) cases in group A and 10 (15.6%) cases in group B ( p = 0.687 ). Overall incontinence was reported in 3 (4.6%) cases in group A and 18 (27.7%) cases in group B ( P = 0.001 ). The total St. Mark's scores for incontinency of group A ( 0.092 ± 0.52 ) and group B ( 1.8 ± 02.47 ) significantly differed ( p < 0.001 ). Conclusions: The "Jump technique", named after a runner who jumped over hurdles, has obviated these complications. The "Jump technique" had satisfactory results and can be utilized as a first-line approach for all types of fistulas. Moreover, it can be redone for cases with recurrences without affecting the continence, paving the way to change the technique during operations.